'As resilient as an ironweed:' narrative resilience in nonprofit organizing. Issue 5 (2nd September 2020) - Okamoto, Kristen E.
ABSTRACT: This study explores the organizing strategies of a nonprofit organization working to address rural food insecurity. I worked alongside Sustainable Appalachia, a nonprofit organization operating to create sustainable food systems for the people of Appalachia Ohio. Through ethnographic-based research I worked with this organization over the course of one year by volunteering as a clerk at a produce auction, working in community gardens, and attending planning meetings. Throughout these activities I collected discourse, including participant observation field notes, semi-structured interviews, promotional materials, and participatory sketching. Within and through these discourses, I began to shape the theoretical concept of narrative resilience. As I explain, narrative resilience is place-based, heroic, and pragmatic. I end by offering ways in which this framework may be particularly useful to applied communication scholars interested in the study of resilience and nonprofit organizing.